Can Real Property Law Play a Role in Addressing Housing Vulnerability? The Case of Older Women Experiencing Housing Stress and Homelessness - Travia, B.; Webb, Eileen (2015)
There is much discussion about the shortage of affordable housing in Australia and the rising tide of homelessness. Perhaps surprisingly to some, older women are one of the fastest growing groups of people experiencing homelessness. In the aftermath of a lifetime of income inequality and taking 'time out' for caring responsibilities, older women may be in a precarious position should they encounter illness, divorce or unemployment in mid to older age. This article outlines the background to the growing number of older women experiencing homelessness and, although the authors are not suggesting the law can provide 'the answer' to this multi-faceted conundrum, the article examines possible contributions the law could make in alleviating some pitfalls encountered by older women experiencing housing stress or homelessness.